Relationship on Education Level and Mother's Attitudes About Exclusive Association With Nutritional Status of Children - Mulyadi Mulyadi (Eduvest - Journal of Universal Studies, 2021)
The magnitude of the problem of malnutrition in infants is a health problem for citizens in Indonesia. This research aims to analyze the relationship between knowledge and behavior of mothers about breastfeeding and exclusive breastfeeding with the nutritional status of infants aged 6- 24 months. This research used a quantitative observational analytic method with a cross sectional approach. The research population consisted of 98 mothers and toddlers aged 6- 24 months in Kayu Raja Village, Keritang Indragiri Hilir Subdistrict and 78 illustrations, using random sampling method. The questionnaire instrument for information on the level of learning, behavior and exclusive breastfeeding as well as the baby's nutritional status used the BPJS Health Card information. The results of the analysis show the bonding level of learning (p = 0, 011 OR = 25, 196; 95% CI = 2, 087 to 304, 158), behavior (p = 0, 044; OR = 21, 656; 95% CI = 1 , 081 to 434, 028) and exclusive breastfeeding (p = 0, 029; OR = 19, 769; 95% CI = 1, 361 to 287, 238) as well as all variables (Nagelkerger R Square of 68.2% ). There is a significant positive relationship between the level of learning and behavior of mothers about breastfeeding and exclusive breastfeeding with the nutritional status of infants aged 6- 24 months.